Sperm flagellum volume determines freezability in red deer spermatozoa - Ros-Santaella, José Luis; Domínguez-Rebolledo, Alvaro Efrén; Garde, José Julián (PloS one, 2014)
The factors affecting the inter-individual differences in sperm freezability is a major line of research in spermatology. Poor sperm freezability is mainly characterised by a low sperm velocity, which in turn is associated with low fertility rates in most animal species. Studies concerning the implications of sperm morphometry on freezability are quite limited, and most of them are based on sperm head size regardless of the structural parts of the flagellum, which provides sperm motility. Here, for the first time, we determined the volumes of the flagellum structures in fresh epididymal red deer spermatozoa using a stereological method under phase contrast microscopy. Sperm samples from thirty-three stags were frozen and classified as good freezers (GF) or bad freezers (BF) at two hours post-thawing using three sperm kinetic parameters which are strongly correlated with fertility in this species. Fourteen stags were clearly identified as GF, whereas nineteen were BF. No significant difference in sperm head size between the two groups was found. On the contrary, the GF exhibited a lower principal piece volume than the BF (6.13 µm3 vs 6.61 µm3, respectively, p = 0.006). The volume of the flagellum structures showed a strong negative relationship with post-thawing sperm velocity. For instance, the volume of the sperm principal piece was negatively correlated with sperm velocity at two hours post-thawing (r = -0.60; p<0.001). Our results clearly show that a higher volume of the sperm principal piece results in poor freezability, and highlights the key role of flagellum size in sperm cryopreservation success.
Keywords: analýza hlavních komponent; kryoprezervace; Deer; vysoká zvěř; spermie; zmrazování; Cryopreservation; Organelles; Microscopy, Phase-Contrast; hlavička spermie; Freezing; Sperm Motility; Sperm Head; Cluster Analysis; bičík spermie; zvířata; Principal Component Analysis; mikroskopie fázově kontrastní; Kinetics; Epididymis; organely; motilita spermií; Male; Semen Preservation; shluková analýza; epididymis; uchování spermatu; Spermatozoa; Animals; mužské pohlaví; kinetika; Sperm Tail